Enhanced antibacterial efficacy of nitric oxide releasing thermoplastic polyurethanes with antifouling hydrophilic topcoats. (3rd May 2017) - Singha, Priyadarshini; Pant, Jitendra; Goudie, Marcus J.; Workman, Christina D.; Handa, Hitesh
Abstract : Hydrophilic antifouling topcoat combined with nitric oxide releasing polymer to enhance antimicrobial efficacy and combat healthcare-associated infections caused by medical devices. Abstract : Surface fouling is one of the leading causes of infection associated with implants, stents, catheters, and other medical devices. The surface chemistry of medical device coatings is important in controlling and/or preventing fouling. In this study, we have shown that a combination of nitric oxide releasing hydrophobic polymer with a hydrophilic polymer topcoat can significantly reduce protein attachment and subsequently reduce bacterial adhesion as a result of the synergistic effect. Nitric oxide (NO) is a well-known potent antibacterial agent due to its adverse reactions on microbial cell components. Owing to the surface chemistry of hydrophilic polymers, they are suitable as antifouling topcoats. In this study, four biomedical grade polymers were compared for protein adhesion and NO-release behavior: CarboSil 2080A, silicone rubber, SP60D60, and SG80A. SP60D60 was found to resist protein adsorption up to 80% when compared to the other polymers while CarboSil 2080A maintained a steady NO flux even after 24 hours (∼0.50 × 10 −10 mol cm −2 min −1 ) of soaking in buffer solution with a loss of less than 3% S -nitroso- N -acetylpenicillamine (SNAP), the NO donor molecule, in the leaching analysis. Therefore, CarboSil 2080A incorporated with SNAP and top-coated with SP60D60 was tested for antibacterial efficacy after exposure to fibrinogen, an abundantly found protein in blood. The NO-releasing CarboSil 2080A with the SP60D60 top-coated polymer showed a 96% reduction in Staphylococcus aureus viable cell count compared to the control samples. Hence, the study demonstrated that a hydrophilic polymer topcoat, when applied to a polymer with sustained NO release from an underlying SNAP incorporated hydrophobic polymer, can reduce bacterial adhesion and be used as a highly efficient antifouling, antibacterial polymer for biomedical applications.